IBRAHIM ŞINASI EFENDI'S JOURNALIST IDENTITY AND THE TASVIR-I EFKÂR NEWSPAPER - İNCU, Nurcan (Atlas Journal, 2020)
Tasvir-i Efkâr newspaper is the continuation of the first special Turkish newspaper Tercüman-ı Ahvâl. It also has a very important role in the Turkish press. This newspaper which is published in Turkish, in contrast to other newspapers at that time; includes many innovations. İbrahim Şinasi Efendi, the owner of the newspaper and known as the father of Turkish opinion journalism, is one of the leaders of the intellectuals who helped for the first special newspapers to be published. He repeated his views in the first issue of Tercüman- Ahvâl newspaper, also in Tasvir-i Efkâr newspaper and he stated that the purpose of the publication was to inform the public, to teach the public to consider their own benefits and to focus on their own problems. Tasvir-i Efkâr newspaper, which included important figures of Turkish modernization under its administration; compares the norms in the west with the Ottoman innovation movements and defends them against absolute power. This work; examines the place and importance of Tasvir-i Efkâr newspaper, which started in 1862 and continued its publishing life for about seven years in the history of the Turkish press, trough the subjects it has covered and its founder İbrahim Şinasi Efendi's intellectual journalist identity.